An API of APIs: a content silo mashup for library websites - Hannan, Sean (Online Searcher, 2015)
At Johns Hopkins University, silos are at the base of their battle with web content. Our philosophy about library content has been to put our content where our users already are. Minor content updates became a full-day workload of managing multiple content management systems and custom applications. This approach was unsustainable. Once they identified this issue, their goal became to decouple Web site content from the platforms on which it was displayed. What we actually needed was our own API that could bundle all these external services together under one umbrella. Rapier is what we call our API of APIs. It provides con- tact information, service and building hours, lists of subject guides, lists of licensed databases, tweets, and blog content across our platforms. Rapier is around 300 lines of Ruby code. Just 300 little lines allow us to pull the bulk of our content from six different content silos.